Incidence of Gastric Cancer in Patients with Laryngeal Cancer - Ji-Hyun Seo; Hyun-Jin Kim; Jung Je Park; Ok-Jae Lee; Jin Pyeong Kim; Seong-Ki Ahn; Jeong Seok Hwa; Jong Sil Lee; Hee-Shang Youn (Yong Chan Lee, 2017)
Background/Aims: Gastric cancer (GC) is the second most common cancer in Korea and the most common in men in the south of the country. We investigated the incidence of synchronous GC in patients with head and neck squamous cell carcinoma (HNSCC) in the southern part of Korea. Materials and Methods: We retrospectively reviewed the medical records of HNSCC patients treated between 2011 and 2014. In patients with synchronous GC, evaluation included a history of smoking and alcohol consumption, endoscopic findings, Campylobacter-like organism (CLO) test, and immunohistochemical analysis of preserved HNSCC tissues. Results: Analysis of the records of 153 HNSCC patients revealed tumors of the larynx in 56 patients (36.6%), of the pharynx in 74 patients (48.4%), and tumors at other locations in 23 patients (15.0%). The mean age of patients was 66.0 years, and the men:women ratio was 8:1. Synchronous cancers were detected in 12 patients. We observed esophageal squamous cell carcinoma (SCC) in five patients (3.3%), and gastric adenocarcinoma in seven patients (4.6%). Synchronous GC was detected in patients with laryngeal SCC. All cases of GC were classified as early GC. Conclusions: Synchronous GC was as frequent as esophageal SCC in patients with HNSCC, and all cases of GC were observed to be early stage cancers in this study. Thorough endoscopic examination should be performed in patients with laryngeal cancer to detect the presence of synchronous GC.